Validation of an Automated Symptom-Based Triage Tool in Ophthalmology - Meer, Elana; Ramakrishnan, Meera S.; Whitehead, Gideon; Leri, Damien; Rosin, Roy; VanderBeek, Brian (Applied Clinical Informatics, 2023)
Objectives Acute care ophthalmic clinics often suffer from inefficient triage, leading to suboptimal patient access and resource utilization. This study reports the preliminary results of a novel, symptom-based, patient-directed, online triage tool developed to address the most common acute ophthalmic diagnoses and associated presenting symptoms.Methods A retrospective chart review of patients who presented to a tertiary academic medical center's urgent eye clinic after being referred for an urgent, semi-urgent, or nonurgent visit by the ophthalmic triage tool between January 1, 2021 and January 1, 2022 was performed. Concordance between triage category and severity of diagnosis on the subsequent clinic visit was assessed.Results The online triage tool was utilized 1,370 and 95 times, by the call center administrators (phone triage group) and patients directly (web triage group), respectively. Of all patients triaged with the tool, 8.50% were deemed urgent, 59.2% semi-urgent, and 32.3% nonurgent. At the subsequent clinic visit, the history of present illness had significant agreement with symptoms reported to the triage tool (99.3% agreement, weighted kappa = 0.980, p < 0.001). The triage algorithm also had significant agreement with the severity of the physician diagnosis (97.0% agreement, weighted kappa = 0.912, p < 0.001). Zero patients were found to have a diagnosis on exam that should have corresponded to a higher urgency level on the triage tool.Conclusion The automated ophthalmic triage algorithm was able to safely and effectively triage patients based on symptoms. Future work should focus on the utility of this tool to reduce nonurgent patient load in urgent clinical settings and to improve access for patients who require urgent medical care.
Keywords: urgent care; ophthalmic emergency; triage; automated triage tool; symptom-based triage tool